Students go through the gears at the iGEM competition for engineering biology - Lawrence,J; Chang,S; Rodriguez,LC; Ouldridge,T (The Biochemist, 2019)
The annual International Genetically Engineered Machine (iGEM) competition, represents an exciting opportunity for students to experience first-hand the potential of synthetic biology approaches to solve real-world problems. In this article, an iGEM team based at Imperial College London share some of the highlights from their participation in the 2018 iGEM event, including sharing their work at the annual Jamboree in Boston, Massachusetts.